2017
DOI: 10.1177/0748233717724983
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to polyhexamethylene guanidine phosphate from humidifiers in residential settings: Cause of serious lung disease

Abstract: Exposure to the humidifier disinfectant, polyhexamethylene guanidine phosphate (PHMG), in mists generated from ultrasonic humidifiers was studied in a simulation chamber and apartment rooms. PHMG is suspected as a causative agent of lung disease in Korea residences. In the simulation-chamber study, the amount of disinfectant discharged from three different ultrasonic humidifiers was measured. Mists generated at 1, 2, and 4 times the recommended amount of disinfectant were sampled with an impinger, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
3
8
0
Order By: Relevance
“…As shown in Figure , the dramatic drop in cell viability was recorded for the physical blend of PHMG and PPU. The observed toxicity is attributed to the leaching of the unbonded PHMG oligomers into the culture medium, and its adverse effect on humans cells. , Indeed, the highly water-soluble characteristic of PHMG is responsible for its leaching and subsequent uptake by both cell membranes and bacteria, leading to cell toxicity and biocidal activity in a dissolved form. The chemical anchoring of PHMG to the UPU backbone at the proper concentration provided copolymers with excellent selectivity for killing bacteria over mammalian cells, as proved from the biocidal activity and MTT assay.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure , the dramatic drop in cell viability was recorded for the physical blend of PHMG and PPU. The observed toxicity is attributed to the leaching of the unbonded PHMG oligomers into the culture medium, and its adverse effect on humans cells. , Indeed, the highly water-soluble characteristic of PHMG is responsible for its leaching and subsequent uptake by both cell membranes and bacteria, leading to cell toxicity and biocidal activity in a dissolved form. The chemical anchoring of PHMG to the UPU backbone at the proper concentration provided copolymers with excellent selectivity for killing bacteria over mammalian cells, as proved from the biocidal activity and MTT assay.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Forty-eight published studies using non-human animal subjects or in vitro toxicology studies were included in the review ( Table 3 ). 16 39 40 41 42 43 44 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 To investigate the hazardous effects of humidifier disinfectants, in vitro studies were performed using various cell lines, and toxicity tests were performed using several animal models. Cytotoxicity, lung fibrosis, and pulmonary genotoxicity due to PHMG exposure were described as a consequence of toxicity testing undertaken shortly after HDLI was reported.…”
Section: Resultsmentioning
confidence: 99%
“… 39 Although controversial, experimental tests revealed that when a humidifier disinfectant was sprayed, it could be deposited in the lungs. 40 60 61 62 The incidence of HDLI increased with the estimated exposure concentration and the distance to the humidifier in an investigation conducted on a group of subjects who were using humidifier disinfectants. 10 41 42 63 Even though an HDLI outbreak resulted in a substantial number of deaths, the effects were reversible in some people who were exposed to the humidifier disinfectant.…”
Section: Discussionmentioning
confidence: 99%
“…A rodent study has reported that intratracheal instillation or inhalation of PHMG phosphate induces severe lung inflammation and fibrosis, similar to the pathological features in affected humans [7][8][9]. The aerosol form of PHMG (nano-sized PHMG) that is released by humidifiers can penetrate and accumulate deep in the lungs [10]. The analysis of the pathological, radiological and clinical features of HDLI cases, and lung histopathology of HD-exposed experimental animals, led to the refinement of the diagnostic criteria for HDLI in 2013 [11,12] (Tables 1 and 2).…”
Section: Introductionmentioning
confidence: 93%